Trigger Warning: What to do with the ugly history that lurks in your archives - Rogova, Irina; Coleman, Tara L.; Hight, Cliff (My University, 2021)
So you’ve encountered materials in your institutional collection showcasing histories of racism, sexism, and other forms of bigotry. You’ve gone through the process of appraising these materials, describing them, and making them accessible to the public. You’ve even added a content warning to your collections to let researchers know they may encounter offensive materials. What now? In this audio piece, three information professionals from Kansas State University will tackle the “what’s next” of working with controversial collection materials. The speakers will then guide listeners through some of the legal and ethical requirements for archivists seeking to highlight these materials and we will discuss how to use these materials to create learning opportunities for our students, faculty, and staff.